Calculation of welded shell structures under dynamic loading - MAKARENKO, Valeriy; JELEZNYAK, Igor (Ways to Improve Construction Efficiency, 2025)
Today, a topical issue is the calculation of shell structures at risk of corrosion cracking, which should be carried out according to the permissible bearing load based on the strength of the critical stresses that cause the appearance and development of a corrosion crack at the maximum permissible depth of a corrosion crack or crack type defect. The usual calculation of the bearing load of structures made of ductile materials, including low-carbon steels, is carried out without taking into account the final weld stresses according to the permissible stresses. As a rule, the actual cracks detected, in the presence of which the devices still remain stable, exceed the calculated ones. This is due to the appearance, as a rule, not of single cracks, but of a series of cracks, which leads to de-concentration of stresses and an increase in critical crack sizes. Calculations using fracture mechanics in the presence of a series of cracks require both scientific and experimental substantiation. However, from the above example calculation, it follows that residual stresses can dramatically reduce the critical size of a corrosion crack. Along with the considered approach, taking into account the advantages and limitations discussed earlier for predicting the serviceability of welded structures with initial non-failures and other defects, it is advisable to use calculations based on the methods of fracture mechanics. For this purpose, the expressions for determining the stress intensity factor, material characteristics K1SSC and K1C, as well as the characteristics of crack growth under specific loading conditions should be known. With these data obtained from pilot tests, the following tasks can be solved a) to give a comparative assessment of materials according to the criteria of K1SSC and K1C, ceteris paribus, materials with a higher value of these coefficients have greater resistance to fracture; b) based on the values of K1SSC and K1C known for a given material and environment and the value of stresses acting in the structure, calculate the permissible size of crack-like defects, based on the condition of non-propagation of the crack (according to K1C) c) limit the permissible acting stresses based on the known K1SSC and K1C and defects in the structure; d) calculate the failure-free service life of products under specific loading conditions for a given metal-medium pair based on the known critical combination of stresses, defect size and velocity characteristic.